2012
DOI: 10.1371/journal.pone.0039191
|View full text |Cite
|
Sign up to set email alerts
|

Murine Gut Microbiota Is Defined by Host Genetics and Modulates Variation of Metabolic Traits

Abstract: The gastrointestinal tract harbors a complex and diverse microbiota that has an important role in host metabolism. Microbial diversity is influenced by a combination of environmental and host genetic factors and is associated with several polygenic diseases. In this study we combined next-generation sequencing, genetic mapping, and a set of physiological traits of the BXD mouse population to explore genetic factors that explain differences in gut microbiota and its impact on metabolic traits. Molecular profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
192
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(203 citation statements)
references
References 69 publications
7
192
2
2
Order By: Relevance
“…However a recent study with 416 twin pairs demonstrated that MZ twins have greater overall microbial community similarities than DZ twin pairs and identified several microbial taxa with relative abundances that differ depending on host genetics (Goodrich et al 2014). Studies using genetic crosses of mice, where the environment can be controlled, also suggest that host genetics can significantly alter gut microbiota composition (Benson et al 2010;McKnite et al 2012;Srinivas et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However a recent study with 416 twin pairs demonstrated that MZ twins have greater overall microbial community similarities than DZ twin pairs and identified several microbial taxa with relative abundances that differ depending on host genetics (Goodrich et al 2014). Studies using genetic crosses of mice, where the environment can be controlled, also suggest that host genetics can significantly alter gut microbiota composition (Benson et al 2010;McKnite et al 2012;Srinivas et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of quantitative trait locus regions reported to regulate microbial abundance contain genes related to immunity and maintenance of barrier function. [225][226][227] The influence of immune-related genes is further evidenced by the dramatic effects on microbial community structure caused by mutations in single genes related to host immunity. 228,229 As an example, mice genetically deficient in the gut mucosal expression of innate immune system modulators (Toll-like receptor 5) developed insulin resistance even in the absence of increased obesity, 217 and high fecal calprotectin levels have been found to be indicative of an inflammatory colonic environment.…”
Section: Inflammation and The Microbiomementioning
confidence: 99%
“…Several groups have reported that enteric microbial composition is a heritable trait, 234,235 although results from twin studies have shown discordant evidence of heritability. 236 However, studies using naturally occurring genetic variation among panels of inbred mouse strains and single gene mutations in genetically modified mice have consistently shown an effect of host genetics on intestinal microbial community structure 225,226,[237][238][239][240] and may have increased power to detect genotype-driven microbial differences. This is especially relevant because murine studies allow tight control over environmental factors, including diet.…”
Section: Host Genetics and Microbial Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…This exclusion is not to imply that host genetics play no role. Well-controlled quantitative trait loci mapping studies in mice indicate that microbiota composition is affected by host genetic factors, including those involved in immune responses, as well as by environmental exposures (18,19). Although studies of dizygotic and monozygotic twins suggest that the representation of members of the gut community is impacted by genotype (11,20), genomewide surveys are needed to address the important question of the contributions of host genetics versus environment on microbiota structure and function.…”
Section: A Model Of Microbial Inheritancementioning
confidence: 99%